Illness Impact on Marriage and Level of Loneliness for Women Diagnosed with Gynecologic Cancer - (:unkn) unknown (SPRINGER, 2015)
This study is conducted to determine the illness impact on marriage and level of loneliness for women diagnosed with gynecologic cancer. All of the patients (n:95) who have been admitted to the gynecologic oncology clinic of a private education-research hospital, which is located in Istanbul in Turkey, between June 2012 and June 2013 were included in the study. Permission from the institution's ethic board and consent from the patients were taken prior to the application. Data were collected by the socio-demographic data survey and the UCLA-LS Loneliness Scale whose validity and reliability studies were made by Demir (1989) in Turkey. Data were evaluated by the numerical percentage calculations and Kruskal-Wallis and Mann-Whitney U tests. The mean age of the patients 51.2 +/- A 12.4 and the mean duration of their marriage 27.4 +/- A 13.1 years. 41.1 % of the patients have ovarian cancer and 50.5 % of them being treated for ovarian cancer for < 1 year. It was determined that 47.7 % of the patients were undergoing chemotherapy treatment for < 6 months and 44.2 % of them had 1-6 cycles of chemotherapy. 47.4 % of the patients stated that they have seen no change in the attitude of their husbands towards them. 13.7 % of the patients think that their husbands want to leave them, 29.5 % of them think that their husbands spend more time their businesses, 25.3 % of them think that their husbands are drifting away from their homes and 12.6 % of them think that their husbands start to come home late than before. 78.9 % of the patients stated that their sexual lives changed after the diagnosis and 47.4 % of them stated that they felt lonely. 57.9 % of the patients stated that their husbands were less supportive during the illness and 54.7 % of them stated that they need psychological support. It was determined that the loneliness level of the patients who were in the young age group, who had more than seven cycles of chemotherapy, who stated that their sexual lives changed after the diagnosis and who were thinking that their husbands drifted away from them and their homes during the illness is higher than the other patients (p < 0.05).
Keywords: Gynecologic cancer; Marriage; Loneliness; Turkey; QUALITY-OF-LIFE; BREAST-CANCER; ISSUES